Cervix Cancer in Sub-Saharan Africa: An Assessment of Cervical Cancer Management. (2021) - Burt, Lindsay M.; McCormak, Mary; Lecuru, Fabrice; Kanyike, Daniel M.; Bvochora-Nsingo, Memory; Ndlovu, Ntokozo; Scott, Aba A.; Anorlu, Rose I.; Sharma, Vinay; Plante, Marie; Nyongesa, Catherine; Tigeneh, Wondemagegnehu; et al.
Abstract : PURPOSE: Underdeveloped nations carry the burden of most cervical cancer, yet access to adequate treatment can be challenging. This report assesses the current management of cervical cancer in sub-Saharan Africa to better understand the needs of underdeveloped nations in managing cervical cancer. METHODS: A pre- and postsurvey was sent to all centers participating in the Cervical Cancer Research Network's 4th annual symposium. The pre- and postsurvey evaluated human papillomavirus and HIV screening, resources available for workup and/or treatment, treatment logistics, outcomes, and enrollment on clinical trials. Descriptive analyses were performed on survey responses. RESULTS: Twenty-nine centers from 12 sub-Saharan countries saw approximately 300 new cases of cervical cancer yearly. Of the countries surveyed, 55% of countries had a human papillomavirus vaccination program and 30% (range, 0%-65%) of women in each region were estimated to have participated in a cervical cancer screening program. In the workup of patients, 43% of centers had the ability to obtain a positron emission tomography and computed tomography scan and 79% had magnetic resonance imaging capabilities. When performing surgery, 88% of those centers had a surgeon with an expertise in performing oncological surgeries. Radiation therapy was available at 96% of the centers surveyed, and chemotherapy was available in 86% of centers. Clinical trials were open at 4% of centers. CONCLUSION: There have been significant advancements being made in screening, workup, and management of patients with cervical cancer in sub-Saharan Africa; yet, improvement is still needed. Enrollment in clinical trials remains a struggle. Participants would like to enroll patients on clinical trials with Cervical Cancer Research Network's continuous support.